دور الشفافية المحاسبية و معايير الإفصاح المحاسبي الدولي في الحد من الفساد المالي : دراسة محاسبية تحليلية - د. فيحاء عبد الخالق البكوع; منهل مجيد; ارسلان ابراهيم الافندي (PROSPECTIVE RESEARCHES, 2023)
This Current research aims at studding the role of accounting disappearance and the adherence of the internal accounting disclosure standers to limit l the effect of financial deterioration in the economic entities. The problem of the research is in the misuse of disappearance. The research has come up with a number of conclusions. The most important one is that the accounting dispersant which assures the accounting lists should contain important, essential and enough dater which enable all users to evaluate their future decisions and limit the level of the appropriate disclose. Finally the research submitted number of recommendations to the logic support to the methods of financial observation and its devices and to put procedures to reduce the financial deterioration.